2006
DOI: 10.1111/j.1746-1561.2006.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Sustainability of the Healthy Learners Asthma Initiative

Abstract: The Healthy Learners Asthma Initiative (HLAI) involved collaboration between Minneapolis Public Schools (MPS), local health care providers/payors, parents, and other partners. The intervention included development of enhanced asthma care in school health offices and clinic performance improvement projects to foster adoption of National Institutes of Health asthma guidelines. Goals were to improve asthma management among school children and reduce asthma‐related school absences, hospitalizations, and emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 10 publications
0
64
0
Order By: Relevance
“…Second, school health staff attempt to obtain written asthma treatment plans for each student's overall asthma management from the provider and family, thus both ensuring the development of such a plan and establishing some degree of partnership among the school, the family, and the provider. [26][27][28][29] Most efforts to establish or improve access to continuing care for asthma in the community by school nurses or other health personnel have not been very successful. 27 Although case detection efforts have been shown to increase awareness of asthma cases by school staff, most schools have found it difficult to influence the relationship between family and health care providers beyond providing instructions for rescue care during the school day.…”
Section: Strategies To Improve Access To Carementioning
confidence: 99%
“…Second, school health staff attempt to obtain written asthma treatment plans for each student's overall asthma management from the provider and family, thus both ensuring the development of such a plan and establishing some degree of partnership among the school, the family, and the provider. [26][27][28][29] Most efforts to establish or improve access to continuing care for asthma in the community by school nurses or other health personnel have not been very successful. 27 Although case detection efforts have been shown to increase awareness of asthma cases by school staff, most schools have found it difficult to influence the relationship between family and health care providers beyond providing instructions for rescue care during the school day.…”
Section: Strategies To Improve Access To Carementioning
confidence: 99%
“…The successful implementation and continuation of the HLAI demonstrated that a comprehensive community-based model of care that includes schools can improve the management of pediatric asthma in a community (Erickson et al, 2006 [this issue, p. 319]; Splett et al, 2006). Positive evaluation data provided evidence to justify continuation of the HLAI in MPS.…”
Section: Implementation Of the Healthy Learner Modelmentioning
confidence: 99%
“…However, research suggests that if children receive evidence‐based care that includes school health services, the rate of school attendance among children with asthma can equal that of children without asthma (Splett et al . , Millard et al . ).…”
Section: Introductionmentioning
confidence: 99%